Inovasi Waistcoat Pria Kombinasi Plain Weave - Nur Hidayati, Imania; Suhartini, Ratna (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to combine the results of the waistcoat design development and the resulting waistcoat with a combination of plain weave. This research method uses the Double Diamond Model which consists of 4 stages, namely, Discover, Define, Develop, and Deliver. In the initial stage, look for sources of ideas, collect inspiration to make a moodboard. The second stage is to create a moodboard according to the ideas that have been determined. The third stage is developing a waistcoat design with a combination of selected plain weave motifs. The fourth stage is the final stage of data collection by testers and fashion experts. Data collection techniques in the research process use observation sheets. The data analysis technique uses quantitative descriptive analysis techniques using mean or average values. The results of the research show that innovation in waistcoat design with a combination of plain weave can increase the unique and functional value of clothing, providing exploration value in the development of men's clothing with aspect values of 1-4 resulting, namely from the design suitability aspect getting an average value of 4.23, the principle aspect the design received an average value of 4.15, the aspect of suitability of the design with the finished product received an average value of 4.23, and the usability aspect received an average value of 4.15. The results of data collection and analysis show that the design and finished product of the plain weave combination waistcoat was stated to be of interest to the observers and received a good average score.